1983
DOI: 10.2307/1890580
|View full text |Cite
|
Sign up to set email alerts
|

The City and the Saloon: Denver, 1858-1916

Abstract: Book Reviews 159 rhetoric outruns the evidence. Happily these shortcomings do not emerge large in what is otherwise a commendable work on a not-often-studied subject.For the reader interested in the questions of charitable and cultural philanthropy in Chicago and elsewhere, Noblesse Oblige is a worthy addition to the scholarly literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This geographical concentration resulted primarily from the city's "segregated vice" policy, in which officials allowed music-centered saloons, variety theaters, brothels, and gambling houses to operate with minimal police interference as long as they remained within the designated vice and entertainment districts. 33 Also during the 1870s, the music at both basic music saloons and concert saloons expanded beyond minstrelsy to include Victorian piano tunes, operatic overtures and arias, and popular European orchestral music. 34 This shift in music coincided with a shift away from African American musicians.…”
Section: The Origin Of Chicago's Music Saloonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This geographical concentration resulted primarily from the city's "segregated vice" policy, in which officials allowed music-centered saloons, variety theaters, brothels, and gambling houses to operate with minimal police interference as long as they remained within the designated vice and entertainment districts. 33 Also during the 1870s, the music at both basic music saloons and concert saloons expanded beyond minstrelsy to include Victorian piano tunes, operatic overtures and arias, and popular European orchestral music. 34 This shift in music coincided with a shift away from African American musicians.…”
Section: The Origin Of Chicago's Music Saloonsmentioning
confidence: 99%
“…He based this conclusion on a few scathing newspaper exposés and a blatantly anti-saloon reform tract written by a Methodist minister titled Chicago's Dark Places. 67 At best, these contemporary sources are problematic and inconclusive. 68 The recent digitalization of newspapers has made available less biased sources that enable more finely grained research into the social history of nineteenth-century saloons.…”
Section: The Significance Of Female Patronsmentioning
confidence: 99%
“…In his study of the saloon in restrictive Boston and permissive Chicago, Perry Duis demonstrated significant local variation between cities. 7 Similarly, Peter Thompson asserts the primacy of local context in differentiating the tavern life of colonial Philadelphia from that in New England, the Chesapeake, and the Carolinas. Ethnic and religious heterogeneity heightened cultural and political competition, a tendency that accelerated as the city's hitherto prosperous economy declined toward the end of the eighteenth century.…”
mentioning
confidence: 99%
“…Politicians, once in office, depended on saloonkeepers (and the powerful liquor industry behind them) to contribute to their campaign coffers and to help deliver the saloon vote at election time. 19 The unwritten code of reciprocity also governed workers' use of the saloonkeepers' celebrated free lunch. 16 Saloons and politics were so thoroughly intertwined that many saloonkeepers themselves became machine politicians, such as Michael "Hinky Dink" Kenna, who ran a Chicago barroom significantly called the "Workingmen's Exchange" and, with his partner, "Bathhouse John" Coughlin, ran much of Chicago as well from the 1890s to the late 1930s.…”
mentioning
confidence: 99%